IMPACT OF LEVERAGE BUYOUT (LBO) AND MANAGEMENT BUY OUT (MBO) ON COMPANIES - Nuzul Kurniawan; Raja Hafiz Hermawan; Hendriyan Syahputra; Hendra Aris; Indrayani; Muammar Khaddafi; Damsar (RADJA PUBLIKA, 2023)
Based on previous research, researchers analyzed the impact of LBO and MBO on company performance. The research method used is qualitative research with descriptive analysis techniques through a literature review. This research focuses on collecting empirical data and information related to the impact of LBO and MBO. The results showed that LBO can significantly affect company performance by increasing profitability, sales growth, and operational efficiency. External factors such as economic conditions and industry competition, as well as internal factors such as management quality, changes in ownership structure, and incentive systems, influence the long-term success of LBOs. However, risks such as reduced profitability and operational efficiency also need attention. on the other hand, MBO positively impacts a company's operational performance, including increasing profits, profit margins, and efficiency. MBO often occurs when economic policy uncertainty increases and can result in favorable purchase prices and significant operational improvements. However, MBO is not consistent in increasing the performance of companies that fail through MBO, and tax factors also affect the value and performance of companies in the context of MBO. Overall, MBO has the potential to increase company performance, value, and productivity, but structural changes need attention. MBO is not consistent in increasing the performance of companies that fail through MBO, and tax factors also affect the value and performance of companies in the context of MBO. Overall, MBO has the potential to increase company performance, value, and productivity, but structural changes need attention. MBO is not consistent in increasing the performance of companies that fail through MBO, and tax factors also affect the value and performance of companies in the context of MBO. Overall, MBO has the potential to increase company performance, value, and productivity, but structural changes need attention.